Why is sex so rare in Lecane inermis (Rotifera: Monogononta) in wastewater treatment plants?. Issue 2 (2nd April 2014) - Pajdak‐Stós, Agnieszka; Fiałkowska, Edyta; Kocerba‐Soroka, Wioleta; Sobczyk, Mateusz; Fyda, Janusz
Abstract The monogonont rotifer Lecane inermis is commonly known as a facultative parthenogen. Unexpectedly, among numerous lineages we isolated from wastewater treatment plants (WWTP), only one was capable of sexual reproduction. We investigated why sex was so rare among L. inermis in WWTP. The reproductive modes of lineages derived from the sexual lineage were examined. Among all lineages, the fraction of those reproducing only asexually for 14 d was 0.39. In the subsequent round, the fraction of asexual lineages reached 0.61. The population growth rate of the parthenogenetic lineages was significantly higher than that of the sexual lineages. We simulated the fate of rotifer populations in WWTP by removing 10% of the experimental cultures each day. After 10 d of these conditions, the mean number of females was greater in parthenogenetic than in sexual lineages. After 20 d, only solitary dormant eggs remained in the sexual lineages. It therefore appears that the loss of sex may be attributed to the specific conditions of the WWTP. When there is no risk of desiccation and no need for dormancy, the fast‐growing parthenogens outcompete lineages investing in costly sex. Furthermore, even if some resting eggs were deposited, they would be washed out from the system with the excess sludge.